The level of Bumiputera awareness towards Unit Trust Investment: a case study in Permodalan Nasional Berhad / Amirah Bisyarah Azizan - Azizan, Amirah Bisyarah (Faculty of Business and Management, 2010)
Every single company needs strategies in order to survive or to become a leader in the market nowadays, therefore a study towards findings the suitable strategies for Permodalan Nasional Berhad had been carried out. The purpose of the study is to identify the level of Bumiputera awareness towards unit trust investment, to identify the factors contribute to level of Bumiputera awareness towards unit trust investment and to examine the most effective factor contribute to level of Bumiputera awareness.